The Clash of Rural and Urban Values in the Comic Books Budak Kampung and Mat Som: (Pertembungan Nilai Desa dan Kota dalam Buku Komik Budak Kampung dan Mat Som) (Malay Literature, 2020)
Lat, whose real name is Mohammad Nor Khalid, is a distinguished and versatile figure among cartoonists in Malaysia. His comic books tend to record sociocultural issues in Malaysia and often show the realities of Malaysian life, especially that of the rural Malay community. Comics are not just reading material for entertainment but are also an important medium for conveying ideas, criticisms and insights as well as having the ability to expose various disparities in local communities. This paper will look into the clash of rural and urban values in two of Lat's comic books entitled Budak Kampung (1979) and Mat Som (1989). The objective of this paper is to analyse the clash of values between rural and urban communities and explain the use of comic elements in conveying meanings in both comics. This paper will use the theory of sociology of literature developed by Alan Swingewood (1972), which is a sociocultural approach to the production of literary works. The findings of this study show that Lat's childhood experiences influenced the creation of Budak Kampung, while his young adulthood experiences influenced the creation of Mat Som. The clash of rural and urban values are tremendously significant in both works, as depicted by the entry of tin mining companies, selling of land, choosing a spouse, clothing styles and way of thinking.Keywords: comic, clash of values, sociocultural influence, Budak Kampung, Mat Som